PRIVATIZATION AND FIRM PERFORMANCE: A COMPARATIVE STUDY OF DEVELOPING AND DEVELOPED COUNTRIES - Jeffits Khusnu Alif (Suluh Adiluhung Publisher (SAPub), 2025)
Privatization, the transfer of ownership from public to private entities, remains a controversial topic. Proponents argue that privatization enhances efficiency, innovation, and management, while critics highlight risks such as job losses and declines in public service quality. This study examines the impact of privatization on corporate performance, particularly in developing countries, using a bibliometric analysis of literature from 2005 to 2013. The results show that privatization in developing countries tends to focus on short-term gains due to fiscal pressures and political instability, while in developed countries, privatized firms struggle to convert R&D investments into market value. The success of privatization depends on institutional readiness, strategic planning, and supportive regulations. Policymakers must balance short-term gains with long-term impacts to ensure sustainable benefits.